On the Oil and Gas Source Rocks Classification - M. A. Bolshakova; A. V. Stoupakova; R. S. Sautkin; K. A. Sitar; A. G. Kalmykov; E. A. Krasnova; N. V. Pronina; A. P. Vaytekhovich (Georesursy, 2025)
The paper is devoted to the classification of oil and gas source rocks. Determination or prediction of the characteristics of oil and gas source sediments is one of the key factors in assessing the prospects and forecasting the oil and gas potential of a particular region. In the paradigm of the sedimentary-migration theory of oil and gas formation, an adequate assessment of the amount and properties of organic matter in sedimentary rocks is the key to an adequate calculation of oil and gas resources. The article presents an overview of approaches to ranking oil and gas source rocks based on various parameters and proposes a new comprehensive approach to the classification of oil and gas source rocks that generate oil and gas. An attempt was made to combine the characteristics of the mineral part and organic matter of oil and gas source strata in a new general classification. The prediction of the properties of oil and gas source sediments is based on the conditions of accumulation of these strata. The proposed classification can be used to assess the prospects for oil and gas potential, especially in conditions of insufficient data on potential oil and gas source sediments.